1991
DOI: 10.1093/geronj/46.3.p127
|View full text |Cite
|
Sign up to set email alerts
|

Word Onset Gating and Linguistic Context in Spoken Word Recognition by Young and Elderly Adults

Abstract: Young and elderly adults heard recorded words that increased in word-onset duration ("gated" words). Without context, both age groups could recognize spoken words after hearing only 50% to 60% of word onset information. When these words were embedded in sentence contexts, subjects required only 20% to 30% of word onset for recognition. An analysis of pre-recognition responses was used to examine use of linguistic context by both age groups to produce correct word recognition in the absence of a complete, or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
1
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 0 publications
13
79
1
1
Order By: Relevance
“…First, older listeners, in general, are better able to use contextual cues to predict the final word in the sentence. This is consistent with a number of other studies demonstrating equivalent or better use of supporting linguistic context by older listeners relative to young listeners (e.g., Wingfield et al, 1991Wingfield et al, , 1994Pichora-Fuller et al, 1995;Humes et al, 2007). Second, older listeners perform worse when the task demands impose a relatively higher cognitive load (i.e., repeating several elements in a sentence versus repeating a single word).…”
Section: A Age Differences For Processing Words and Sentences In Noisesupporting
confidence: 90%
“…First, older listeners, in general, are better able to use contextual cues to predict the final word in the sentence. This is consistent with a number of other studies demonstrating equivalent or better use of supporting linguistic context by older listeners relative to young listeners (e.g., Wingfield et al, 1991Wingfield et al, , 1994Pichora-Fuller et al, 1995;Humes et al, 2007). Second, older listeners perform worse when the task demands impose a relatively higher cognitive load (i.e., repeating several elements in a sentence versus repeating a single word).…”
Section: A Age Differences For Processing Words and Sentences In Noisesupporting
confidence: 90%
“…The reduced context benefit was evidenced by three findings: (1) compared to the normal-hearing young adults, the young adults in whom we simulated a hearing impairment benefited less from context; (2) the older participants benefited less from context than the young normal-hearing adults; and (3) among the older listeners, we found that the more hearing-impaired participants were, the less benefit they gained from context. These context findings complement the robust finding of older listeners' increased reliance on semantic context (Nittrouer & Boothroyd, 1990;Pichora-Fuller et al, 1995;Sheldon, Pichora-Fuller, & Schneider, 2008;Sommers & Danielson, 1999;Wingfield, Aberdeen, & Stine, 1991). In most of these semantic context studies, standardised Sentence-Perception-In-Noise materials (SPIN-R) were used in which the sentence-final word is either highly predictable from the preceding semantic context, or has a low predictability (Bilger, Neutzel, & Rzeczowski, 1984;Kalikow, Stevens, & Elliott, 1977).…”
Section: Discussionsupporting
confidence: 61%
“…For instance, Wingfield et al ͑1991͒ examined the ability of young and elderly listeners to recognize words increased in word-onset duration ͑"gated" words͒. They found that both groups need 50% to 60% of the word-onset information to recognize the "gated" words without context, but only 20% to 30% when the words are embedded in sentence context.…”
Section: B Effect Of Linguistic Factorsmentioning
confidence: 99%